PENGARUH PROFITABILITAS, KEBIJAKAN HUTANG, KEBIJAKAN DEVIDEN, DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN (Studi Kasus Perusahaan Manufaktur Yang Go Publik di Bursa Efek Indonesia) PERIODE 2010 - 2014 - Hari Purnama (Jurnal Akuntansi, 2016)
Singer study aims to review the empirical buktik ABOUT determine the effect of profitability (ROE) The Company Value (PBV). For a review of empirical know buktik ABOUT influence Debt Policy (DER) Against Corporate Value (PBV). For a review of empirical know buktik ABOUT influence Dividend Policy (DPR) The Company Value (PBV). For a review of empirical know buktik ABOUT influence Investment Decision (PER) Against Corporate Value (PBV). For a review of empirical know buktik ABOUT influence profitability (ROE), Debt Policy (DER), Dividend Policy (DPR), and Investment Decisions (PER) operates simultaneously Against Corporate Value (PBV). Research Variables The singer is the effect of profitability (ROE), Debt Policy (DER), Dividend Policy (DPR), and Investment Decisions (PER) and Corporate Value (PBV). Research Data Data operates is sekuder Form Manufacturing Company Financial Statements Year period 2010 - 2014. The analysis technique used is multiple linear regression WITH significance level of 5%. Results showed profitability (ROE) and a significant positive effect Against Corporate Value (PBV). Debt Policy (DER) No effect Against Corporate Value (PBV). Dividend policy (DPR) and a significant positive effect Against Corporate Value (PBV). Investment Policy (PER) and a significant positive effect Against Corporate Value (PBV). Concurrent operating profitability (ROE), the policy Debt (DER), the dividend policy (DPR) and kebjakan Investments (PER) significantly Against Corporate Value (PBV). Effect profitability (ROE), the policy Debt (DER), the dividend policy (DPR) and kebjakan Investments (PER) The Company Value by 56.6% while the rest influenced by factors lying Its NOT SIGN Model Research hearts. Keywords: Profitability, Debt Policy, Dividend Policy, Investment Policy and Corporate Value